Managing Waiting Times and Providing Equitable, Family-Centred Care: A Description of Four Key Initiatives from NHS Fife Child Health Occupational Therapy Service (2006–11). (August 2013) - Millar, Fiona; Doherty, Maria; Forster, Gladys; McFarlane, Aileen; Ogilvie, Pippa
Equity, timeliness and family-centredness are key dimensions of high-quality occupational therapy service delivery. This practice analysis reflects on practice-based initiatives to achieve these. In 2006, the National Health Service Fife Child Health Occupational Therapy Service, in the United Kingdom, had extensive waiting times, which varied across the region, and high levels of service user dissatisfaction related to these. To address this, the service investigated ways to make better use of the existing resources and adopted the Care Aims framework, culminating in quality improvement initiatives. Key initiatives were: triaging new referrals, health promotion, care agreements with service users and extending the health care support worker's role. The main challenges encountered were staff anxiety and the expectations of both service users and other professionals. Important facilitators were dynamic leadership and well-motivated staff. Following implementation, waiting times were reduced and are, at the time of writing, consistently less than 12 weeks. Anecdotal evidence suggests that service user satisfaction has improved.